Assistência estudantil do IFMT - Câmpus Rondonópolis : imposições da pandemia à frágil política de permanência - Silva, Dilma Ferreira Leite (2023)
This dissertation aims to analyze the institutional strategies/actions of the IFMT Student Assistance, at the Rondonópolis Campus, aimed at ensuring the permanence of students during the Covid-19 Pandemic, in the period from 2020 to 2021.The interest in this study was determined by the concerns resulting from the professional experience, lived with the Student Assistance Policy. This is a qualitative study that does not exclude the recurrence of quantitative data. To accomplish it, it was initially resorted to the bibliographic and documentary survey and, in a second moment, the application of questionnaires applied through the google forms platform, in which the link was made available, via e-mail, to the students benefiting from the student permanence aid of the Integrated High School of the IFMT Campus Rondonópolis. Thus, this dissertation was structured in three sections: 1) Professional and Technological Education in Brazil; 2) Student assistance in the federal network; and 3) Challenges of Student Assistance in times of pandemic. It was based on the understanding that Student Assistance has played a relevant role in confronting educational inequalities, aiming to contribute to the permanence of students and aiming at the prevention of school dropout. The conclusion reached with this study is that despite the challenges posed by the health crisis, the strategies and actions carried out by IFMT, Rondonópolis Campus, during the Covid-19 pandemic, contribute for the permanence of students in the courses.